Assessing the Educational Quality of Facebook Videos as an Informative Resource on Otitis Media. (January 2021) - Kahn, Chase I.; Wang, Rita; Shetty, Kunal; Huestis, Mikayla J.; Cohen, Michael B.; Levi, Jessica R.
Objective: This study analyzes the quality and reliability of otitis media (OM) videos on Facebook and investigates whether the videos shared within the Facebook community are considered to be a valuable educational tool. The results of this study are important for providing clinicians with the necessary understanding about the video content that their patients may be exposed to. Study Design: Cross-sectional analysis of video content. Setting: A new Facebook account was created to carry out a search for videos on OM. Methods: Inclusion criteria were as follows: videos intended for educating patients or guardians on OM, videos in the English language, and videos with at least 1 share. Results: A total of 364 videos were screened, and 62 fit our inclusion criteria for analysis. The majority (56%) of OM videos on Facebook focused on complementary and alternative medication without mentioning any current guidelines. A limited amount of videos (29%) made any mention to surgical treatment options for OM. There was a strong positive correlation (rho = 0.8419, P < .001) between a video's content and its reliability. There was no correlation seen between a video's content and its shares (rho = −0.142, P = .1359). Conclusions: The majority of OM videos on Facebook are inadequate for educational value. Clinicians should know about the existence of videos on OM and the quality of information that parents are exposed to.